Software system for 3D capturing, analysis and display - Patel, Dhwani (Nanyang Technological University, 2024)
3D reconstruction is an important area of computer vision research and has gained popularity in various fields such as robotics, medical imaging, autonomous vehicles, etc. This paper aims to understand popular methods of 3D point cloud registration, highly useful method for 3D reconstruction of an object from all angles. Specifically, it will explore ICP registration and its implementation in 2 ubiquitous programming languages Python and MATLAB. Research papers will be explored and the advantages and limitations of these techniques will be discussed. Overall, this study contributes to a better understanding of the strengths and weaknesses of MATLAB and Python implementations for ICP registration, providing valuable insights for future research and development efforts in point cloud processing and 3D reconstruction.